2014
DOI: 10.1128/cvi.00105-14
|View full text |Cite
|
Sign up to set email alerts
|

Performance of a Cytomegalovirus IgG Enzyme Immunoassay Kit Modified To Measure Avidity

Abstract: bThe measurement of cytomegalovirus (CMV) IgG avidity accurately discriminates recent and past CMV infections. We sought to determine if the Wampole Laboratories CMV IgG enzyme immunoassay (EIA) could be modified to measure avidity. The evaluation panel consisted of 156 serum samples we used in 2002 to validate a laboratory-developed EIA, in which 78 serum samples exhibited low avidity, 7 exhibited intermediate avidity, and 71 exhibited high avidity. The qualitative agreement between the two avidity assays was… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
11
0

Year Published

2014
2014
2023
2023

Publication Types

Select...
5

Relationship

2
3

Authors

Journals

citations
Cited by 10 publications
(11 citation statements)
references
References 27 publications
0
11
0
Order By: Relevance
“…This information, in conjunction with the CMV avidity maturation timeline discussed earlier, suggests that patients with IgM persistence will exhibit an IgM-positive but high-CMV-avidity result set if tested more than 5 to 6 months postinfection. This result pattern is common among patients being evaluated for possible primary CMV infection; core study groups found that about 50% of CMV IgM-positive at-risk patients had high CMV IgG avidity (27,28,33), a percentage confirmed by other investigators (13,15,22). Thus, some pregnant women with an IgM-positive/high-IgG-avidity result set may actually have nonrecent primary CMV infection in a setting of IgM persistence, rather than viral reactivation/reinfection.…”
Section: Studies Of CMV Igg Avidity During Pregnancymentioning
confidence: 79%
See 2 more Smart Citations
“…This information, in conjunction with the CMV avidity maturation timeline discussed earlier, suggests that patients with IgM persistence will exhibit an IgM-positive but high-CMV-avidity result set if tested more than 5 to 6 months postinfection. This result pattern is common among patients being evaluated for possible primary CMV infection; core study groups found that about 50% of CMV IgM-positive at-risk patients had high CMV IgG avidity (27,28,33), a percentage confirmed by other investigators (13,15,22). Thus, some pregnant women with an IgM-positive/high-IgG-avidity result set may actually have nonrecent primary CMV infection in a setting of IgM persistence, rather than viral reactivation/reinfection.…”
Section: Studies Of CMV Igg Avidity During Pregnancymentioning
confidence: 79%
“…Antigen-bound low-avidity IgG, but not high-avidity IgG, dissociates from the antigen in the presence of mild protein denaturants, such as urea, potassium thiocyanate, and guanidine chloride. The most common test format is an enzyme-linked immunosorbent assay (ELISA) utilizing urea as the dissociating agent (14,21,22). The patient's diluted serum is added to two microtiter wells coated with CMV antigen; after incubation, one well is washed with regular wash buffer, whereas the other well is washed with wash buffer containing urea.…”
Section: Definition Of Avidity and Basic Methodologymentioning
confidence: 99%
See 1 more Smart Citation
“…The study utilized 369 consecutive CMV IgG-positive serum samples submitted to the Focus Diagnostics Reference Laboratory for CMV IgG avidity testing (16); 91% of these samples were supplied by women of childbearing age (15 to 49 years old), but no clinical data were available for any of the patients who supplied the serum samples. Following release of the avidity results, the samples were deidentified before the various IgM assays were performed.…”
Section: Specimensmentioning
confidence: 99%
“…The serum samples were tested for CMV IgG avidity using a commercially available CMV IgG EIA kit (Wampole Laboratories, Princeton, NJ) with modifications as described in the accompanying article (16). Briefly, a given sample was diluted per the package insert and added to two microtiter wells; after incubation, one well was washed with kit-supplied wash buffer and the other well was washed with dissociating buffer (wash buffer containing 6 M urea).…”
Section: Specimensmentioning
confidence: 99%